Performance Crime and Justice - Surette, Raymond (Current issues in criminal justice, 2015)
Due to enhanced audience participation and involvement in content creation and distribution, crime and justice has changed. This change came about with the emergence of new digital social media and is reflected in the growth of crime and justice performances. Performances today are ephemeral renditions created and distributed in millions of social media interactions. The irony is that performances previously were created for wide heterogeneous audiences, but access was limited by time, place and medium. In contrast, new media performances are usually directed at smaller homogeneous audiences, but access is potentially unlimited due to their digital nature. In this new social media reality, the altered nature of a performance has important implications for crime and justice. Whereas crime traditionally was comprised of low visibility events in which the actors strove to hide their identities, in the new media world surreptitious crime competes with a growing number of high-visibility crimes. This article explores how the associated evolution of performance has affected crime, law enforcement and the judicial system. The impact of performance crime and justice will continue to stress criminal justice systems and change the way crime and justice is experienced in the 21 st century.